Telemedicine for trauma, emergencies, and disaster management - Latifi, Rifat; Poropatich, Ronald; Hadeed, George J. (Artech House, 2011)
Telemedicine has evolved to become an important field of medicine and healthcare, involving everything from simple patient care to actual performance of operations at a distance. This groundbreaking volume addresses the complex technical and clinical development in the management of trauma, disaster, and emergency situations using telemedicine. The book explains how telemedicine and related technologies can be used to effectively handle a wide range of scenarios, from a situation as small as a car crash, to major disasters such as an earthquake. Professionals find critical discussions on the p.